2020
DOI: 10.24201/edu.v36i1.2078
|View full text |Cite
|
Sign up to set email alerts
|

Características étnico-raciales y desigualdad de oportunidades económicas en México

Abstract: El presente trabajo examina la asociación entre las características étnico-raciales y los resultados económicos en México. A partir de datos del Módulo de Movilidad Social Intergeneracional 2016, levantado por el INEGI (2017) como parte de la Encuesta Nacional de los Hogares, nuestros hallazgos indican que todas las características étnico-raciales estudiadas (autoadscripción, lengua indígena y tono de piel) se asocian de manera estadísticamente significativa con los destinos económicos de las personas, siendo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
3
22
0
6
Order By: Relevance
“…The percentage of the population in Mexico that self-identifies as indigenous is 21·5 (8) . Almost 70 % of the indigenous population live in poverty, 43 % have not completed primary education and 55·2 % work in low-skilled manual jobs (9,10) .…”
mentioning
confidence: 99%
“…The percentage of the population in Mexico that self-identifies as indigenous is 21·5 (8) . Almost 70 % of the indigenous population live in poverty, 43 % have not completed primary education and 55·2 % work in low-skilled manual jobs (9,10) .…”
mentioning
confidence: 99%
“…Instead, stratification research has focused on mixed-raced individuals and their position vis-à-vis other ethnoracial categories, with positions varying by national case (see, for example, Telles and PERLA 2014). In Mexico, research has revealed that mestizos have the highest levels of education, even compared to whites (Martínez Casas et al 2014; Solís, Güémez, and Holm 2019).…”
Section: Multiracialism Inequality and Dual Ethnoracial Minoritiesmentioning
confidence: 99%
“…Recent studies of the intersection of race/ethnicity/phenotype and gender in Mexico suggest that intersectionality is an important lens for understanding inequality. Compared to indigenous men and non-indigenous women, indigenous women suffer higher levels of socioeconomic disadvantage (Bonfil Sánchez et al 2017; Comisión Económica para América Latina y el Caribe [CEPAL] 2014; Consejo Nacional de Evaluación de la Política de Desarrollo Social [CONEVAL] 2014), especially those who speak an indigenous language and/or have darker skin (Arceo-Gomez and Campos-Vazquez 2014; Solís, Güémez, and Holm 2019). Indigenous women have also been found to suffer high levels of physical, political, structural, and emotional violence (Bonfil Sánchez et al 2017; CEPAL 2014).…”
Section: Intersectionality and Dual Ethnoracial Minoritiesmentioning
confidence: 99%
See 2 more Smart Citations